2017
DOI: 10.1177/1039856217711054
|View full text |Cite
|
Sign up to set email alerts
|

Embedding exercise interventions as routine mental health care: implementation strategies in residential, inpatient and community settings

Abstract: There is an emergence of PA interventions being imbedded within a variety of mental-health settings. These interventions vary in terms of mode and intensity of service delivery. Yet, all aim to increase PA and reduce sedentary behaviour. Adopting the identified strategies may help facilitate successful implementation and increase access to PA interventions for mental-health service users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 32 publications
1
42
0
2
Order By: Relevance
“…Regular physical activity and exercise have been found to prevent stress-related diseases (Harber et al, 2017;Li & Siegrist, 2012) and strengthen mental health (Hearing et al, 2016;Lederman et al, 2017;Schulz et al, 2012). These benefits are due to several factors, including a preventive effect whenever exercise contributes to lowered stress perceptions (Gerber et al, 2014) and a coping-promoting effect when exercise helps to endorse adaptive coping behaviours (Cairney et al, 2014).…”
mentioning
confidence: 99%
“…Regular physical activity and exercise have been found to prevent stress-related diseases (Harber et al, 2017;Li & Siegrist, 2012) and strengthen mental health (Hearing et al, 2016;Lederman et al, 2017;Schulz et al, 2012). These benefits are due to several factors, including a preventive effect whenever exercise contributes to lowered stress perceptions (Gerber et al, 2014) and a coping-promoting effect when exercise helps to endorse adaptive coping behaviours (Cairney et al, 2014).…”
mentioning
confidence: 99%
“…The inpatient environment provides an opportunity to regulate physical activity into daily routine, however, the potential for exercise implementation is often not reached in this environment (Blythe & White, 2012). Consequently, there is a growing need to address the systemic barriers which have impeded widespread implementation of physical activity interventions (Lederman et al 2017). Additionally, it has been recognised that the delivery of such interventions in inpatient settings is challenging, and the evidence, although promising, is limited (Stanton & Happell, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Exercise and sport have been successfully employed to treat a wide range of psychiatric disorders [13], and are considered essential to human wellbeing [14]. Although the UNHCR (United Nations High Commissioner for Refugees, Geneva, Switzerland) recognizes the potential of exercise and sport as a peace-building measure in refugee camps [15], and reviews have shown that increased physical activity has positive effects on traumatized individuals [16,17], very limited evidence is available regarding the potential of exercise and sport as part of the treatment of refugees suffering from PTSD symptoms [18].…”
Section: Introductionmentioning
confidence: 99%